?EFFECT OF CEMENT DUST POLLUTION ON THE GROWTH OF SOME TREE SPECIES (Biological Sciences - PJSIR, 1995)
Effect of cement dust ondry weight of Albizia lebbeck, Leucennea leucocephala and Thespesia populneoides was observed as compared to control (unpolluted) plants. Height, number of leaves, leaf area and biomass of T. populneoideswzs affected,whilereductioninplantdryweight,coverandleafareainA.Lebbeck and 1..Leucocephala was comparatively less affected than theother species investigated.